The Resonance of Anti-Black Violence in the Great Outdoors - Tyeshia Redden (Land, 2025)
The events of 2020 reached a fever pitch with the May 25th murder of George Floyd, but earlier on the same morning, a chance encounter between dogwalker Amy Cooper and birding enthusiast Christian Cooper also laid bare enduring social relations. As video footage of the encounter spread across social media, it sparked both public outrage and discourse regarding Black nature enthusiasts. Employing a historical-interpretive method informed by conversation analysis and guided by “whiteness as property,” I assemble news articles, social media posts, and video footage to analyze the events in Central Park and their aftermath. To unsettle existing paradigms regarding who we imagine are entitled to the great outdoors, I identify potential collaborative partners across scales who can further the goals of education, recruitment, and visibility for Black nature enthusiasts and professionals. I demonstrate how expanding environmental justice to include anti-Black racial violence allows us to recognize that the specter of lynching defies geographic boundaries, diffusing across space and time, occasionally coalescing to defend white privilege and historic racial orders.